Implementation of Hypnobreastfeeding Therapy as an Effort to Reduce the Incidence of Underweight on Children Aged 0–6 Months - Laily, Nur; Rahman, Fauzie; Putri, Andini Octaviana; Noor, Meitria Syahadatina; Rahayu, Atikah; Yulidasari, Fahrini; Anggraini, Lia; Anhar, Vina Yulia; Sari, Ayu Riana; Rosadi, Dian; Afifah, Afifah; Azmiannoor, Muhammad; et al. (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aims to identify implementation of hypnobreastfeeding therapy as an effort to reduce the incidence of underweight on children aged 0–6 months. METHODS: This study is a pre-experimental with pre-test and post-test design. Subjects were children aged 0–6 months who are underweight. The intervention was conducted over 2 months. Data were analyzed by univariate analysis using frequency distribution table and bivariate using McNemar test. RESULTS: Before the education through hypnobreastfeeding therapy, only 33.3% of women having a good attitude about exclusive breastfeeding to children. After the intervention for 2 months, the percentage of good attitude increase as many as 73.3% and the mother is encouraged to continue to breastfeed the child obtained that a total of 18 children (60%) of the total 30 children aged 0–6 months are underweight, which has been entered into the category of normal nutritional status. A difference in the attitude of breastfeeding and status of underweight children aged 0–6 months before and after implementation of hypnobreastfeeding therapy (p < 0.000). CONCLUSION: There are differences in the attitude of the breastfeeding mother (p = 0.012) and underweight status of children aged 0–6 months (p = 0.000) before and after the implementation of hypnobreastfeeding therapy.